2000
DOI: 10.2460/javma.2000.216.701
|View full text |Cite
|
Sign up to set email alerts
|

Influence of tumor cell proliferation and sex-hormone receptors on effectiveness of radiation therapy for dogs with incompletely resected meningiomas

Abstract: This study confirms the value of irradiation for dogs with incompletely resected meningiomas. Prognostic value of the PFPCNA index suggests-that duration of treatment and interval from surgery to start of irradiation may affect outcome. Loss of progesterone receptors in some tumors may be responsible for an increase in PFPCNA index and may indirectly affect prognosis after radiation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 42 publications
3
68
1
Order By: Relevance
“…This finding seems to support the fact that metalloproteinase activity is not that strictly related to the proliferative index of neoplastic meningial cells, as conversely demonstrated for PR88. 25,46 The follow-up data showed a survival time of up to 58 months for feline meningiomas submitted to surgery and for canine meningiomas of up to 32 months, even though they were malignant. These findings are more encouraging than those reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding seems to support the fact that metalloproteinase activity is not that strictly related to the proliferative index of neoplastic meningial cells, as conversely demonstrated for PR88. 25,46 The follow-up data showed a survival time of up to 58 months for feline meningiomas submitted to surgery and for canine meningiomas of up to 32 months, even though they were malignant. These findings are more encouraging than those reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a high proliferative index in the tumor is associated with low progesterone receptor (PR) concentration, suggesting that PR expression in canine and feline meningiomas is a reliable prognostic factor in the evaluation of this tumor, as well as in humans. 2,12,25,46 More recently, canine and feline meningiomas have been tested for telomerase immunoreactivity 22,26 and have produced contradictory results as to the correlation with the proliferative index.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to human brain tumors, overexpression of cellular proliferation and apoptosis‐associated markers such as EGFR, PDGFRa, VEGFR1,2, c‐Met, IGFBP2,108, 109, 110, 111 c‐erbB2, pERK, pAkt, Bcl‐2, Bcl‐xL,111 and the angiogenic factor VEGF112, 113, 114, 115, 116 has been reported in both canine gliomas and meningiomas. Decreased progesterone receptor expression has been reported in canine meningiomas associated with higher proliferative indices and poorer prognosis,117, 118 and these features also are associated with increased VEGF expression 114…”
Section: Molecular Diagnosticsmentioning
confidence: 99%
“…Currently available studies highlight the large variation in outcome, and the potential impact of applied technology. In dogs with confirmed meningiomas, standard surgical cytoreduction alone generally has been reported to result in median survival times of approximately 4.5–7 months,144, 145, 146 with an improvement in median survival to 16.5–30 months with adjunctive radiation therapy 118, 145. However, use of cortical resection, ultrasonic aspiration, or endoscope‐assisted techniques has been reported to result in median survival times of 16, 41, and 70 months, respectively, for rostrotentorial meningiomas 146, 147, 148.…”
Section: Surgical Treatmentmentioning
confidence: 99%
“…11 Markers used in meningiomas of domestic species include cytokeratins, estrogen receptor, glial fibrillary acidic protein (GFAP), Ki67, neuron-specific enolase, progesterone receptor, proliferating cell nuclear antigen, S100, synaptophysin, h-telomerase, and vimentin. 1,3,27,28,42,59 Combining the results of 2 large series of canine meningiomas, vimentin was expressed in all (37 of 37), followed by neuron-specific enolase (29 of 37), S100 (28 of 37), GFAP (6 of 37), and cytokeratins (11 of 37). Synaptophysin was not reactive in any case (0 of 15).…”
mentioning
confidence: 99%